Sensibility of Spondias purpurea L. (Anacardiaceae) exposed to fluoride-simulated fog - Anjos, Talles Bruno Oliveira dos; Louback, Eliza; Azevedo, Aristéa Alves; Silva, Luzimar Campos da (Ecological Indicators, 2018)
Fluoride is the atmospheric pollutant with the highest phytotoxicity arising from aluminum smelting fertilizers, glass and, ceramic industry. The most affected plant organ is the leaf, in which the fluoride penetrates through two main ways: absorption by epidermis cuticle or absorption by stomata. Species susceptible to fluoride are potential tools in bioindicator studies because they provide a means for detecting the presence of the pollutant in the environment at a low cost. The aim of this study is to evaluate the sensibility of Spondias purpurea L. (Anacardiaceae) to fluoride through the simulated fog. Simulation was performed by applying 500 ml of solution containing 15 mg L−1 of potassium fluoride per plant for 20 min daily and for 10 consecutive days. The data of leaflet abscission, visual damage, and climate conditions were recorded daily. At the end of the experiment, data from the cell death analysis, electrolyte leakage determination, and accumulation of the fluoride in the dried matter were collected. Moreover, samples for phenolic compound accumulation, anatomical, and micromorphological analyses were collected. After 24 h, the appearance of visible damage was observed in the leaves with fluoride treatment. This damage consisted, mostly, of necrosis, chlorosis, and leaf apical shriveling. The necroses manifested in gray and brown discoloration. Leaf abscission was intense in the young leaves. Microscopic damage consisted of protoplast retraction, phenolic compound accumulation, collapse, hyperplasia, and cell rupture. Turgidity loss, epicuticular wax erosion, and damage of stomata and trichomes beyond the presence of fungal hyphae were noted in the epidermis. Evans Blue detected dead cell groups in the transition region between the necrosis and the apparent healthy area. Fluoride affected the selective permeability of the membrane, which was observed in this study according to the high rate of electrolyte leakage. Plants exposed to fluoride accumulated 14.48 times more fluoride in their leaves than plants in the control group. It follows that S. purpurea is susceptible to fluoride and responds quickly to the presence of this pollutant. Marginal and apical necrosis, presence of phenolic compounds, fluoride accumulation, anatomical alterations, and leaflet abscission in the young leaves are biomarkers of fluoride effects in this species. Therefore, S. purpurea is potentially useful in biomonitoring programs.
Keywords: Leaf anatomy; Atmospheric pollution; Bioindicator; Biomarkers